Combined effects of dietary low molecular weight sodium alginate and Pediococcus acidilactici MA18/5M on growth performance, haematological and innate immune responses of Asian sea bass (Lates calcalifer) juveniles - Ghasem Ashouri (2018)
© 2018 Elsevier Ltd Six weeks feeding trial was conducted to examine the effects of dietary administration of low molecular weight sodium alginate (LMWSA) and Pediococcus acidilactici MA 18/5M (PA) on humoral and mucosal immune responses, haematological parameters and growth performance, of Lates calcarifer juveniles. Fish (12.0 ± 0.2 g) were fed experimental diets as follows: Control (diet 1, basal diet), 5 g kg−1LMWSA (diet 2), 10 g kg−1LMWSA (diet 3), 0.9 × 107CFU g−1PA (diet 4), 5 g kg−1LMWSA + 0.9 × 107CFU g−1PA (Diet 5), and 10 g kg−1LMWSA + 0.9 × 107CFU g−1PA (Diet 6). Results indicated a significant (P < 0.05) increase in innate immune parameters including serum lysozyme, bactericidal, hemolytic and respiratory burst activities as well as mucosal immune responses including lysozyme and bactericidal activities, when diet was supplemented with immunostimulants. Moreover, the combined effects of LMWSA with PA resulted in more pronounced immunological responses compared to the control and singular administration. Red and white blood cell counts significantly increased with either singular or combined administration of LMWSA and PA compared with the control group (P < 0.05). The singular administration of PA and combined supplementation of 5 g kg−1LMWSA with PA significantly increased growth performance and feed intake compared with other experimental groups (P < 0.05). These results indicated that combined administration of LMWSA and PA can be considered as beneficial feed additive and immunostimulant in L. calcarifer juveniles.